Enhancing University Students’ Understanding of Sustainable Development Goals (SDGs) through Participatory Learning with the Connectivity Logistics Activity - Vicheansan, Matee; Duantrakoonsil, Wanwisa; Pattanafuengfo, Sajee; Keesoon, Patiphat; Thongsamut, Maneerat (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This objectives of this research were to: 1) examine the level of students’ understanding of the Sustainable Development Goals (SDGs) before and after participating in the “The Connectivity Logistics” activity, 2) analyze the effects of the activity on enhancing SDG-related understanding through participatory learning, and 3) explore students’ opinions regarding the effectiveness of the activity in promoting the SDGs. The sample group consisted of 100 undergraduate students from the College of Logistics and Supply Chain, Sripatum University, across three campuses: Bangkok, Chonburi, and Khon Kaen. The research employed a mixed-methods approach, including quantitative data collection via a 10-item SDG comprehension questionnaire (pre-test and post-test), a 15-item opinion survey on the activity, and qualitative data from in-depth interviews with seven students. The findings revealed the level of understanding of students of the SDGs, with mean scores increasing from 6.23 before the activity to 8.12 after the activity (out of 10). The evaluation of student opinions indicated high levels of satisfaction across all dimensions (mean scores ranging from 4.06 to 4.35 out of 5), particularly in experiential learning in community settings. In-depth interviews confirmed the activity’s role in inspiring students, raising awareness, and empowering them to contribute to sustainable societal development. The results align with Kolb (1984) theory of experiential learning, which emphasizes hands-on practice, reflection, and cognitive processing to enhance understanding. This approach bridges the gap between theoretical knowledge and practical application. Moreover, the activity was designed in accordance with the SDG framework, which promotes integrated environmental, social, and economic dimensions.